A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae) - Salata, Sebastian; Borowiec, Lech (Zootaxa, 2015)
Oxyopomyrmex André, 1881 is a small genus of myrmicine ants found in arid grasslands of the Mediterranean region. Here we provide a new taxonomic revision of the genus. Twelve species are recognized, including five new to science: O. laevibus sp. nov. (Greece: Crete), O. magnus sp. nov. (Spain), O. negevensis sp. nov. (Israel) O. polybotesi sp. nov. (Greece: Nisyros, W Turkey) and O. pygmalioni sp. nov. (Cyprus). Oxyopomyrmex santschii var. nigripes Santschi, 1907 and O. santschii var. nitidior Santschi, 1910 are raised to species level. The following new synonymies are proposed: O. krueperi Forel, 1911 = O. lagoi Menozzi, 1936 syn. nov.; O. nigripes Santschi, 1907 = O. sabulonis var. rugocciput Santschi, 1923 syn. nov. = O. emeryi var. brunnescens Santschi, 1929 syn. nov.; O. nitidior Santschi, 1910 = O. emeryi var. laticeps Santschi, 1915 syn. nov. = O. emeryi st. sabulonis Santschi, 1915 syn. nov.; O. saulcyi Emery, 1889 = O. santschii Forel, 1904 syn. nov. = O. santschii var. siciliana Karavaiev, 1912 syn. nov. = O. gaetulus Santschi, 1929 syn. nov. = O. saulcyi var. latinodis Santschi, 1939 syn. nov. A neotype for O. oculatus André, 1881 is designated. An identification key based on the gyne, male and worker caste is provided.